2017
DOI: 10.1158/1535-7163.mct-16-0511
|View full text |Cite
|
Sign up to set email alerts
|

The BTK Inhibitor Ibrutinib (PCI-32765) Overcomes Paclitaxel Resistance in ABCB1- and ABCC10-Overexpressing Cells and Tumors

Abstract: Paclitaxel is one of the most widely used antineoplastic drugs in the clinic. Unfortunately, the occurrence of cellular resistance has limited its efficacy and application. The ATP-binding cassette subfamily B member 1 (ABCB1/P-glycoprotein) and subfamily C member 10 (ABCC10/MRP7) are the major membrane protein transporters responsible for the efflux of paclitaxel, constituting one of the most important mechanisms of paclitaxel resistance. Here, we demonstrated that the Bruton tyrosine kinase inhibitor, ibruti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The results of the accumulation and efflux experiments were congruent with the reversal effects of VS-4718 shown in anti-cancer efficacy testing when co-administered with substrate-drugs, suggesting that VS-4718 may increase the accumulation of substrate-drugs in ABCB1- and ABCG2-overexpressing cancer cells by inhibiting the ABCB1- and ABCG2-mediated efflux activity, which led to the decline of IC 50 of substrate-drugs and finally attenuated the ABC transporter-mediated MDR. The results are also consistent with studies of our other small-molecule reversal reagents (Zhang et al, 2017 , 2018 ; Gupta et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the accumulation and efflux experiments were congruent with the reversal effects of VS-4718 shown in anti-cancer efficacy testing when co-administered with substrate-drugs, suggesting that VS-4718 may increase the accumulation of substrate-drugs in ABCB1- and ABCG2-overexpressing cancer cells by inhibiting the ABCB1- and ABCG2-mediated efflux activity, which led to the decline of IC 50 of substrate-drugs and finally attenuated the ABC transporter-mediated MDR. The results are also consistent with studies of our other small-molecule reversal reagents (Zhang et al, 2017 , 2018 ; Gupta et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…24 ABCB1 is frequently upregulated in drug-resistant cancer cells and functions as transporter of various drugs, such as carfilzomib, paclitaxel, methotrexate, doxorubicin and cisplatin. [25][26][27][28][29] XIAP encodes a protein that belongs to a family of apoptotic suppressor proteins. XIAP has been initially identified for its role in blocking apoptosis upon inhibition of the activation of caspase-3, −7 and −9.…”
Section: Discussionmentioning
confidence: 99%
“…The reversal agents including breakpoint cluster region-abelson (BCR-ABL) inhibitors imatinib (STI571) and ponatinib (Lei et al, 2006;Sen et al, 2012), epidermal growth factor receptor (EGFR) inhibitors lapatinib (GW-572016) and gefitinib (Kitazaki et al, 2005;Dai et al, 2008), vascular endothelial growth factor receptor (VEGFR) inhibitors vandetanib and motesanib (Zheng et al, 2009;Wang et al, 2014). However, although it was reported that ibrutinib could antagonize MDR mediated by ABCB1 (Zhang et al, 2017), the study on other BTK inhibitors in reversing MDR mediated by ABCB1-overexpression is still lacking. RN486 is a selective, and reversible inhibitor of BTK.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, BTK inhibitors had multiple off-target effects, especially ibrutinib (Gavriatopoulou et al, 2020;Metzler et al, 2020). Currently, ibrutinib, which was approved by Food and Drug Administration (FDA) for treating mantle cell lymphoma (MCL) and chronic lymphocytic leukemia (CLL) (Zhang et al, 2017), has been reported to have significant effect to improve the efficacy of chemotherapeutic drugs transported by ABCB1 transporter in ABCB1-overexpressing cells (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%